Struvite Crystallization for Ammonium Removal from Cow Urine with Bulkhead Reactor - Luluk Edahwati; Sutiyono; Fauziah Hilda Alvira; Rizqi Rendri Anggriawan (Jurnal Teknik Kimia dan Lingkungan, 2021)
The presence of ammonium content in cow urine waste damages the aquatic ecosystem due to its toxicity. Ammonium content can be reduced by removing it through struvite crystallization. In this study, struvite (MgNH4PO4.6H2O) was formed from the reaction of magnesium, ammonium, and phosphate compounds using a bulkhead reactor. The rate of air moving the solution in the reactor causes ammonium to react with reactants to form struvite. This research was conducted with M : A : P (magnesium ammonium phosphate) molar ratio solution is 3 : 1 : 1 and 0,4 L/min air flow rate with MAP flow rate variation of 8,8; 11; 14,67; 22; 44 ml/min and a temperature variation of 25, 35, 45, 55, 65 ̊C to decrease ammonium content. The faster the MAP flow rate, thelower the ammonium removal efficiency. The efficiency of ammonium removal will increase with increasing temperature. The best results obtained in this study were ammonium removal in the waste of 77.97%. The result of x-ray powder diffraction (XRD) and scanning electron microscope (SEM) is the crystals tested was a struvite with elongated or rod shape. EDAX analysis gave the percentage of components in struvite, namely 14.28% Mg, 10.68% N, and 18.19% P.